In situ neutron diffraction study on the effect of aluminium fluoride on phase transformation of mullite from alumina/clay - Tezuka, Nobuo; Low, It-Meng (Jim); Davies, Ian; Alecu, I.; Stead, R.; Avdeev, M.; Mehrtens, E.; Latella, B. (ASSOCIATION FO IRON AND STEEL INDUSTRY, 2007)
The effect of aluminium fluoride (AIF3) on the phase transformation sequence of mullite (3AI2032Si02) from two different types of kaolin (kaolinite and halloysite) (AI2Si20s(OH)4-2H20) within an alumina (A1203) matrix for a temperature range of 20 - 1500 C was investigated using in situ neutron diffraction. Samples containing a mixture of A1F3 (0 - 5 wt%), AI203 and kaolin were heated up to 1500 C and then furnace cooled. During the heating procedure, one hour neutron diffraction scans were conducted at 600, 900, 1100, 1200, 1300 and 1400 C, followed by six consecutive one hour scans at 1500 C and finally a one hour scan at room temperature upon cooling. The diffraction patterns collected between 1100 and 1500 C were analyzed by Rietveld analysis. The observed phase transformations exhibited a typical sequence found inclay/alumina ceramics. Corundum, mullite and cristobalite were observed. A common feature among the specimens containing different amounts of AIF3 and kaolin was that the content of corundum decreased as the amount of mullite increased, whilst the cristobalite content tended to peak near the temperature where the amounts of corundum and mullite were approximately equal. The mullitization temperature was reduced as the AIF3 content increased for both kaolinite and halloysite. The presence of AIF3 appeared to reduce the onset temperature for mullite nucleation, which is at a much lower temperature compared to that of grain growth. However, AIF3 also seemed to lower densification. Likewise mechanical properties of the resulting specimens were determined.